Isolated fallopian tube torsion: A rare twist with a diagnostic challenge that may compromise fertility - Devi Balasubramaniam; Kavitha Yogini Duraisamy; Malathi Ezhilmani; Saranya Ravi (Wolters Kluwer Medknow Publications, 2020)
Isolated Fallopian tube torsion (IFTT) is a rare entity with utmost important gynecological emergency with difficult preoperative diagnosis. Our aim is to analyze the clinical presentation, risk factors, and management of IFTT. We retrospectively analyzed all patients with intraoperative diagnosis of IFTT in our endogynecological department over a time period of 3 years and 6 months (January 2015-June 2018) in a tertiary level laparoscopic center. The clinical profile of the patients was analyzed and the results formulated. Statistical analysis was done by SPSS system, Version 15.00 (SPSS Inc., Chicago). A total 17 cases were diagnosed with IFTT with or without pathology. The mean age was 28.07 ± 11.3 years. Lower abdominal pain was the most common symptom (88%). About 47% had a history of tubal ligation. Salpingectomy was done in the majority of the patients (82.3%). Detorsion and preservation of the tube was possible in 17.6% of the cases. High index of suspicion is needed to diagnose this rare cause of acute abdomen. Hence, an early intervention can enhance the salvageability of the affected tubes which has a positive impact on the fertility status of the patients. Tubal preservation is the preferred procedure of choice whenever feasible.